The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10875-016-0242-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary Immunodeficiency Diseases in Aguascalientes, Mexico: Results from an Educational Program

Abstract: Educational programs are a fundamental part of the global efforts to increase PID diagnosis and care. To be successful, such programs should include public relations, reach for first-contact physicians, and aim to develop an efficient referral network with molecular diagnostic capability. Enhancing medical knowledge on PID is a successful strategy to improve early diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Among the children that were referred with suspected PID 12.7% of the cases were confirmed [14], which is consistent with the results of other study which showed a PID prevalence 9.9% among those referred for evaluation [15].…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…Among the children that were referred with suspected PID 12.7% of the cases were confirmed [14], which is consistent with the results of other study which showed a PID prevalence 9.9% among those referred for evaluation [15].…”
Section: Plos Onesupporting
confidence: 90%
“…The mean delay from initial symptoms to diagnosis in the patients from our center was 31.5 months (2.6 years), ranging from one to 156 months [16]. Other studies reported the mean delay from initial symptoms to a referral for medical advice at 3.7 years [15]; the mean, depending on a PID category, was from 6 to 56 months, and the range from 1 to 134 months [17]. In our previous study, the longest delay to a diagnosis was in a newly diagnosed 16 yearold patient with AT [16].…”
Section: Plos Onementioning
confidence: 68%
See 1 more Smart Citation
“…[11,12] However, the studies in some PID centers also established the prevalence of CID among the cases. [2,13,14] Not all PID groups are represented in our regional PID registry. Defects in intrinsic and innate immunity, autoinflammatory disorders, and complement deficiencies were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…As the diagnostic delay is still high in our study cohort and similar cohorts around the world, even with different resource settings, we should improve our efforts in order to diminish it. The creation of an educational program for health personnel and general public, could be a promising strategy to achieve this goal, as has been recently shown by a group or researchers in Aguascalientes Mexico [18]. …”
Section: Discussionmentioning
confidence: 99%